Uji Aktivitas Antioksidan Ekstrak Etanol Buah dan Biji Buah Kalangkala (Litsea angulata) asal Kalimantan Selatan: Antioxidant Activity Test of Ethanolic Extract of Kalangkala (Litsea angulata) Fruits and Seeds from South Kalimantan - Revita Saputri; Eka Fitri Susiani (Borneo Journal of Pharmacy, 2018)
Free radicals are atoms or molecules, having one or more unpaired electrons. Increased production of free radicals can cause oxidative stress and cause many pathological conditions, e.g. cancers, heart diseases, and other diseases. The antioxidant can inhibit oxidative stress. Kalangkala (Litsea angulata) usually found in the South Kalimantan that can be used as an antioxidant. The study aimed to determine the antioxidant activity of ethanolic extract of Kalangkala fruits and seeds from South Kalimantan. Antioxidant activity was conducted qualitatively and quantitative uses the method DPPH. The result of the antioxidant activity of ethanolic extract of Kalangkala fruits and seeds qualitatively showed the presence of yellow spots on a purple background at Thin Layer Chromatography (TLC). The result of the activity of ethanolic extract of Kalangkala seeds quantitatively obtained IC50 value was 48.78 ppm and activity of ethanolic extract of Kalangkala fruits quantitatively obtained IC50 value was 243.14 ppm. Ethanolic extract of Kalangkala fruits and seeds from South Kalimantan has antioxidant activity.